Prevalence of h. pylori infection in a portuguese sample of adolescents. - Pereira, Carlos (2015)
BACKGROUND There are some gaps in knowledge of the prevalence and determinants of Helicobacter pylori (H. pylori) infection acquired during childhood. The aim of this study was to estimate the prevalence of H. pylori in a portuguese sample of adolescents using 13C-urea breath test (13C-UBT). PARTICIPANTS AND METHODS A sample of 293 adolescents aged 12 to 18 years old, attending a public school in Sátão, Portugal, was enrolled in this cross-sectional study. A self-administered questionnaire was answered by the adolescents in classroom in order to assess socio-demographic and symptoms. The adolescents were screened for H. pylori infection using the 13C-UBT test and needed to fast for at least one hour before the test. The 13C-UBT test consisted in the exhalation of carbon dioxide in samples before and after swallowing urea labeled with non-radioactive carbon-13. Prevalence was expressed in proportions and compared by the chi-square test. Crude odds ratio (OR) with 95% confidence intervals (CI) were used to measure the strength of association between H. pylori infection and the independent variables. RESULTS The prevalence of H. pylori infection was 40.4% (95%CI= 35.0-46.0). The H. pylori infection was associated with gender (female, OR=1.52, 95%CI=1.0-2.46), age (>15 years, OR=1.78, 95%CI=1.1-3.28) parents´ educational level (>9th grade, OR=1.53, 95%CI=1.0-2.50), alcohol consumption (yes, OR=1.45, 95%CI=1.0-2.36), crowding index (≥1, OR=3.49, 95%CI=1.2-13.83), soft drink consumption (yes, OR=0.48, 95%CI=0.22-0.98). CONCLUSIONS Nearly half of the adolescents were positive for H. pylori infection, suggesting that gastric pathology continues to be considered an important public health problem among the population, including among adolescents.